2015
DOI: 10.1116/1.4922157
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterned polymer surfaces with bactericidal properties

Abstract: Bacteria that adhere to the surfaces of implanted medical devices can cause catastrophic infection. Since chemical modifications of materials' surfaces have poor long-term performance in preventing bacterial buildup, approaches using bactericidal physical surface topography have been investigated. The authors used Nanoimprint Lithography was used to fabricate a library of biomimetic nanopillars on the surfaces of poly(methyl methacrylate) (PMMA) films. After incubation of Escherichia coli (E. coli) on the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
240
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(270 citation statements)
references
References 35 publications
8
240
4
Order By: Relevance
“…This effect was reproduced with similar topographies on both black silicon [8] and PMMA [10]. To achieve antimicrobial nanopillar surfaces on Ti and Ti alloy implants, a fabrication technique is needed that can mimic the dimensions of such surface features found in nature, ideally on arbitrary shaped and porous materials.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This effect was reproduced with similar topographies on both black silicon [8] and PMMA [10]. To achieve antimicrobial nanopillar surfaces on Ti and Ti alloy implants, a fabrication technique is needed that can mimic the dimensions of such surface features found in nature, ideally on arbitrary shaped and porous materials.…”
Section: Introductionmentioning
confidence: 95%
“…This requires contact points between the bacterial cell wall and the surface that are much smaller than the bacteria and with sufficient spacing in between the contact points. Dickson et al [10] suggested that the spacing in between nanopillars should be between 130-380 nm. The nanospikes on our surfaces are more closely packed, but the random arrangement of the spikes means that bacteria can be exposed to sufficient local stress at selected points.…”
Section: E Coli In Vitro Studymentioning
confidence: 99%
“…However, research regarding the capacity for nanopatterned surfaces to attract bacterial attachment is contradictory. Dickson 10 found that lower cell densities were retained on PMMA pillared surfaces following 20 h culture compared to on flat surfaces. In contrast, other research findings have illustrated that the presence of nanofeatures can promote bacterial adhesion.…”
Section: B Topographical Effect On Bacterial Adhesion and Viabilitymentioning
confidence: 99%
“…Two of the most widely studied physical-based strategies for antimicrobial surfaces using micro- 8,9 or nanotopographies [10][11][12][13] are inhibition of microbial attachment (antibiofouling) or contact-killing. An example of an antibiofouling surface is the Sharklet micropattern surface, inspired by shark skin.…”
Section: Introductionmentioning
confidence: 99%
“…This effective nanospike height is consistent with that reported in a number of previous studies, 22,23,27,38,46-48 which suggests that a nanofeature height of $300 nm tends to display a greater level of biocidal activity towards both Gram-negative and Gram-positive bacteria than substrata possessing nanospikes with greater or less height. 22,23,27,38,[46][47][48] The reason for the effectiveness of this 'optimal' peak height in killing bacteria is still largely unknown. The inter-pillar spacing on the substrata used in this study was slightly larger than that of a number of previously reported effective antibacterial surfaces, which would initially suggest that nanofeature height plays an important role in the overall bactericidal behaviour of the substrates.…”
Section: 2526mentioning
confidence: 99%